Review of Jet Grouting Practice around the World (Journal of Engineering, 2023)
This paper aims to make a historical review of jet grouting techniques and encountered problems at different sites in several countries.  This review is a good guide to understanding the performance and limitations of improved soils or lands. The basic concept of jet grouting technology is to use cement as a binder to accelerate the hardening process of an admixture of material grout and soil. The different case history was conducted in both sand soil and clay soil in the horizontal and vertical direction. Other papers on field construction showed that the grout can be gelled within 5-10 minutes. Due to different cases and studies, these will help improve soil by supporting the foundation load with a minimal settlement. The Jet grouting technology can be used in difficult situations, confined and unconfined areas, or places with light equipment. Although the jet grouting technique is an ideal modification technique compared to reinforcement and ground treatment support or serves the foundation, Dams and excavations will save time and cost and increase the bearing capacity.